IMPROVING THE QUALITY OF LEARNING THROUGH SUPERVISION WITH VISIT TECHNIQUES IN SDN BANYU URIP II/363 SURABAYA - Subandi Subandi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2021)
Academic supervision behavior is directly related to and influences teacher behavior. By using academic supervision, supervisors influence teacher behavior so that their behavior is getting better in managing teaching and learning. Then, it can influence students to become good students. Therefore, academic supervision used by the headmaster can increase learning when it is done under principle certain. Thus, the headmaster as a supervisor is required to be competent as a person who guides teachers in improving the learning process. We take the title for our research is Improving The Quality Of Learning Through Supervision With Visit Techniques IN SDN Banyu Urip II/363 Surabaya.        The procedure for implementing academic supervision consists of the following steps: (1) preparation stage, namely (a) prepare instruments and (b) prepare a joint schedule; (2) the implementation stage, namely the implementation of the principal's supervisory observations; (3) reporting stage, namely (a) identify the results of observations during classroom observations, (b) analyze the results of supervision, (c) evaluate together the principal and teachers, and (d) make notes on the results of supervision which are documented as a report; (4) the follow-up stage, namely (a) discussing and making solutions, (b) notifying the results of class visits, and (c) communicating to teachers.Our results show that the process of academic supervision can increase the quality of learning with the percentage of success achieved is 96%.